Investigating in vitro Antioxidant and Anti-Inflammatory Activities of Fromia indica Extracts: A Pilot Study - Perera, Kavisha Kavindi; Gunathilake, Varuni Karunika (Asian Journal of Biological and Life Sciences, 2025)
Background: Sea Stars are a highly abundant source of bioactive compounds but have been relatively understudied compared to other invertebrates. This study examines anti-inflammatory and antioxidant properties of zoo chemicals of Fromia indica marine sea star crude extract. Materials and Methods: F. indica identification was based on morphological characteristics and the Sea Star Crude Extract (SCE) was prepared by methanol and dichloromethane extraction and subsequently tested for the presence of zoo chemicals, in vitro radical scavenging activity by, 2, 2-diphenyl-1-picrylhydrazy (DPPH), and peroxide radicals and anti-inflammatory properties by protein denaturation. Each assay was triplicated, and the results were compared with reference drugs or chemicals where necessary. Results: The findings showed the presence of tannins, saponins, phenols, quinones, sterols, alkaloids, flavonoids, and unsaturated sterols, while anthraquinones were absent. Additionally, the IC50 values for the DPPH and H2O2 radical scavenging assays were 5.67 μg/mL and 3.81 μg/mL, respectively, both surpassing the values obtained for the standard drug Ascorbic acid (IC50-21.66 μg/mL and 9.54 μg/mL, respectively). The in vitro anti-inflammatory activity indicated a dose-dependent negative linear correlation in protein denaturation, yielding an IC50 value of 6.22 μg/mL compared to the value obtained for standard drug ascorbic acid (95.59 μg/mL). Conclusion: Cumulatively, F. indica crude extract contained zoo chemicals, which may result the potential antioxidant properties. Further comprehensive bioactivity-guided fractionation is highly recommended.
Keywords: Antioxidant properties; DPPH Assay; Fromia indica; Starfish